Five million years of Antarctic Circumpolar Current strength variability - Lamy F.; Winckler G.; Arz H. W.; Farmer J. R.; Gottschalk J.; Lembke-Jene L.; Middleton J. L.; van der Does M.; Tiedemann R.; Alvarez Zarikian C.; Basak C.; Brombacher A.; et al. (Nature, 2024)
The Antarctic Circumpolar Current (ACC) represents the world’s largest ocean-current system and affects global ocean circulation, climate and Antarctic ice-sheet stability1–3. Today, ACC dynamics are controlled by atmospheric forcing, oceanic density gradients and eddy activity4. Whereas palaeoceanographic reconstructions exhibit regional heterogeneity in ACC position and strength over Pleistocene glacial–interglacial cycles5–8, the long-term evolution of the ACC is poorly known. Here we document changes in ACC strength from sediment cores in the Pacific Southern Ocean. We find no linear long-term trend in ACC flow since 5.3 million years ago (Ma), in contrast to global cooling9 and increasing global ice volume10. Instead, we observe a reversal on a million-year timescale, from increasing ACC strength during Pliocene global cooling to a subsequent decrease with further Early Pleistocene cooling. This shift in the ACC regime coincided with a Southern Ocean reconfiguration that altered the sensitivity of the ACC to atmospheric and oceanic forcings11–13. We find ACC strength changes to be closely linked to 400,000-year eccentricity cycles, probably originating from modulation of precessional changes in the South Pacific jet stream linked to tropical Pacific temperature variability14. A persistent link between weaker ACC flow, equatorward-shifted opal deposition and reduced atmospheric CO2 during glacial periods first emerged during the Mid-Pleistocene Transition (MPT). The strongest ACC flow occurred during warmer-than-present intervals of the Plio-Pleistocene, providing evidence of potentially increasing ACC flow with future climate warming.